Ambient Advertising: Analyzing its Effectiveness Using an Anti - Smoking Advertisement - Singh, Samarth (Indian Journal of Marketing, 2015)
Ambient advertising is uniquely positioned and builds greater involvement . The current study sheds light on the use of ambient advertising and its successful transmission of an anti - smoking message. The study involved the development of an anti-smoking ambient advertisement and understanding its effectiveness among the youth using a questionnaire, interviews, and observations. The results revealed that the youth were ready to change their intent of getting fascinated by smoking.